Susceptibility Pathways in Fanconi's Anemia and Breast Cancer - D'Andrea, Alan D (The New England journal of medicine, 2010)
Fanconi's anemia is a rare disorder that arises from defective repair of damaged DNA. Of the 13 Fanconi's anemia genes, 3 are breast-cancer–susceptibility genes. One is identical to BRCA2 . Cells from patients with the D1 subtype of Fanconi's anemia and their family members carry biallelic mutations in BRCA2 , and heterozygote members of kindreds with the D1 subtype have an increased risk of breast and ovarian cancer. Studies of a rare disorder can thus illuminate a common disorder. Fanconi's anemia is a rare disorder that arises from defective repair of damaged DNA. Of the 13 Fanconi's anemia genes, 3 are breast-cancer̵1;susceptibility genes. One is identical to BRCA2. Studies of a rare disorder can illuminate a common disorder. The study of rare genetic diseases can lead to insights into the cause and treatment of more common diseases. An example is Fanconi's anemia, a rare disorder of chromosomal instability. Studies of this disorder have elucidated the general mechanisms of bone marrow failure, cancer pathogenesis, and resistance to chemotherapy. There are 13 genes involved in Fanconi's anemia, and 1 of them is identical to the well-known breast-cancer–susceptibility gene, BRCA2 (Table 1). The proteins encoded by these Fanconi's anemia genes cooperate in the recognition and repair of damaged DNA. The genes are inactivated not only in Fanconi's anemia but also in . . .